Analisis Ukuran Celah Katup Terhadap Kinerja Mesin Diesel - Maulana, Herlan; Pranoto, Hadi (Jurnal Teknik Mesin Indonesia, 2024)
The size of the cylinder valve clearance gap is one of the parameters that greatly influences the performance of a Diesel engine. Choosing a valve clearance size that can provide the best performance when the engine undergoes regular maintenance is often a problem, especially for Diesel engines that have been in operation for more than 5 years. The standard valve gap size in engine specifications is 0.4 mm. The aim of this research is to analyze valve gap tension which can save fuel consumption in the Diesel engine type 4JA1 2500. This research method involves collecting data by testing variations in valve gap adjustment and variations in engine speed. Experiments on variations in Diesel engine valve tension with valve gap sizes of 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm and 0.6 mm. The test results show that, compared with valve gap sizes of 0.2 mm, 0.3 mm, 0.4 mm, and 0.5 mm, engine cylinders with a valve gap size of 0.6 mm produce the most optimal performance when used. the lowest specific fuel.